2014
DOI: 10.1111/j.2047-2927.2014.00269.x
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA miR‐371a‐3p in serum of patients with germ cell tumours: evaluations for establishing a serum biomarker

Abstract: SUMMARYAs only 60% of the patients with germ cell tumour (GCT) express the classical markers, new markers as for example microRNAs (miRNAs) are required. One promising candidate is miR-371a-3p, but data are sparse to date. We measured serum levels of miR371a-3p in GCT patients, in controls, and in cases with other malignancies. We also assessed the expression in other body fluids and we looked to the decline of serum miR-371a-3p levels after treatment. miR-371a-3p levels were measured by quantitative polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
71
3
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 28 publications
11
71
3
8
Order By: Relevance
“…130 Subsequently, the expression levels of these tissue-based signatures were measured in serum. [131][132][133][134][135][136] These liquid biopsy data confirmed the potential utility of miRNA measurements for discriminating patients with seminoma or those with nonseminoma from healthy control subjects. A selected set of four miRNAs (miR-371a-3p, miR-372, miR-373 and miR-367) present in the two clusters that showed the highest discriminative power for diagnosis and follow-up of cancer, combined with reference miRNAs (miR-20a and miR-93) and spike-in controls was developed as the 'targeted serum miRNA assay' (TSmiR).…”
Section: [H1] Biofluid Micrornas In Testicular Cancersupporting
confidence: 54%
See 1 more Smart Citation
“…130 Subsequently, the expression levels of these tissue-based signatures were measured in serum. [131][132][133][134][135][136] These liquid biopsy data confirmed the potential utility of miRNA measurements for discriminating patients with seminoma or those with nonseminoma from healthy control subjects. A selected set of four miRNAs (miR-371a-3p, miR-372, miR-373 and miR-367) present in the two clusters that showed the highest discriminative power for diagnosis and follow-up of cancer, combined with reference miRNAs (miR-20a and miR-93) and spike-in controls was developed as the 'targeted serum miRNA assay' (TSmiR).…”
Section: [H1] Biofluid Micrornas In Testicular Cancersupporting
confidence: 54%
“…134,136 Two independent studies, confirmed these promising results for miR-371a-3p as a biomarker for testicular cancer; however these reports only included a limited number of participants. 132,133 A simplified assay for analysing miR371a-3p without endogenous controls was recommended to reduce laboratory work, analytical time and costs. 137 Results of another study confirmed the discriminative ability of serum miR-371a-3p and miR-372 concentrations and also identified numerous novel discriminative serum miRNAs (miR-511, miR-26b, miR-769, miR23a, miR-106b, miR-365, miR-598, miR-340 and let-7a), which were identified using a high-throughput profiling system, but did not validate the results.…”
Section: [H1] Biofluid Micrornas In Testicular Cancermentioning
confidence: 99%
“…pleural effusion fluid. Importantly for testicular neoplasms, seminal plasma apparently also has elevated levels of specific miRNAs compared with controls [103]. These results are very promising and it is likely that miRNA-based assays will be routinely used for diagnosis and follow-up of the patients in not so distant future.…”
Section: Traces Of Gct In Blood: Classical Biochemical Markers and MImentioning
confidence: 53%
“…table 1; for all online suppl. material, see www.karger.com/doi/10.1159/000444303); 6 had been reported earlier [24,25]. In 33 CS1 patients, postoperative CVB samples were available, additionally.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence for the specificity of serum levels of miRs-371-3 for testicular GCT is still equivocal despite the following observations: (1) high serum levels of these miRs in the majority of patients, (2) very low levels in healthy men, (3) in men suffering from non-testicular malignancies and (4) a significant decrease of levels after cure [25]. Another way of confirming the specificity of miRs-371-3 for testicular GCT would be to show particularly high levels of these miRs in body fluids being in close contact to the testicular neoplasm.…”
Section: Introductionmentioning
confidence: 99%